2017
DOI: 10.1038/srep43483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of predatory bacteria on the gut bacterial microbiota in rats

Abstract: Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus are Gram-negative proteobacteria that are obligate predators of other Gram-negative bacteria and are considered potential alternatives to antibiotics. Most studies focusing on predatory bacteria have been performed in vitro, thus the effect of predatory bacteria on a live host, including the impact on the ecology of the native microbiota, has yet to be fully examined. In this study, intrarectal inoculations of Sprague-Dawley rats with predatory bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 55 publications
5
42
0
Order By: Relevance
“…This aspect has been, and continues to be, thoroughly investigated using both human cells and numerous animal models such as zebrafish, mice, rats, rabbits, guinea pigs, and chicks. The results demonstrate an inability of B. bacteriovorus and M. aeruginosavorus to invade mammalian cells, and no apparent pathological effects or signs of cytotoxicity or reduction in cell viability, supporting the proposition that these two BALOs are inherently non-pathogenic to mammals (Westergaard and Kramer, 1977;Atterbury et al, 2011;Dwidar et al, 2012b;Gupta et al, 2016;Willis et al, 2016;Shatzkes et al, 2015Shatzkes et al, , 2016Shatzkes et al, , 2017b. It has even been suggested that B. bacteriovorus may contribute to health as part of the human gut microbiota (Iebba et al, 2013).…”
supporting
confidence: 56%
“…This aspect has been, and continues to be, thoroughly investigated using both human cells and numerous animal models such as zebrafish, mice, rats, rabbits, guinea pigs, and chicks. The results demonstrate an inability of B. bacteriovorus and M. aeruginosavorus to invade mammalian cells, and no apparent pathological effects or signs of cytotoxicity or reduction in cell viability, supporting the proposition that these two BALOs are inherently non-pathogenic to mammals (Westergaard and Kramer, 1977;Atterbury et al, 2011;Dwidar et al, 2012b;Gupta et al, 2016;Willis et al, 2016;Shatzkes et al, 2015Shatzkes et al, , 2016Shatzkes et al, , 2017b. It has even been suggested that B. bacteriovorus may contribute to health as part of the human gut microbiota (Iebba et al, 2013).…”
supporting
confidence: 56%
“…Notably, Paraprevotellaceae, associated with water-only fasting but not FMD treatment, has been previously regarded as pro-inflammatory in the context of IBD, with one study finding it to be especially enriched in mice with severe colitis (Roy et al, 2017). Another study also found Paraprevotellaceae abundance increased in rats with increased pro-inflammatory cytokines, such as IL-13, in colonic tissue (Shatzkes et al, 2017). …”
Section: Discussionmentioning
confidence: 94%
“…The fecal transplant was performed in mice based on previously published protocols (Seedorf et al, 2014; Ellekilde et al, 2014; Kuethe et al, 2016; Shatzkes et al, 2017). Briefly, ceca contents were removed from naive and chronic DSS-induced mice (with or without FMD treatment) and were aseptically flushed into a sterile 50% glycerol/PBS solution, in a 1:10 dilution.…”
Section: Star ★ Methodsmentioning
confidence: 99%
“…But that also means Bdellovibrio could consume beneficial microflora. Preliminary studies by Connell, Kadouri (6), and Sockett 7have found mixed effects. The predators increase numbers of gram-positive species in the gut microbiome of chickens and rats, but whether this imbalance has ill effects on animal health is uncertain.…”
Section: Inside Animal Infectionsmentioning
confidence: 97%